(untitled) (Palimpsesto, 2017)
Eliseo Verón was one of the protagonists of the process of renovation of the social sciences in the 1960s and 1970s in Argentina. His works had contributed to shape a new problematic relating to the mass communication. This article presents an aspect insufficiently explored of his trajectory: it reconstructs and analyzes his role as director in the "Social Sciences Library" of the publishing house Tiempo Contemporáneo (1969-1974). It explores the significance that this Library in the modernization of social sciences, in the emergency of the communication studies and in the promotion of the prestige of Eliseo Verón had. His publisher praxis, is also a fruitful route to examine movements of the field cultural and how Veron experimented their tensions.